Peran Partisipatif Masyarakat Dalam Perencanaan Pembangunan Di Kelurahan Sitokok-Kota Batam - Riyanda, Riko (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2016)
The research is aim at describing the implementation of development planing meeting (Musrenbang) in kelurahan Sitokok, Kecamatan Bulang Kota Batam. Beside of, its aim identifitiying and inhibiting fighters of society role in planing and contructing in kelurahan Setokok. The research used qualitative and descriptive approach. There were two kinds of data taken, first is primary data and second is secondary data. In collecting data, the technique used were observation method, interview method, and documentation method, in analying data, reduction data technique was used furthurmore, the presenting of result of analysis and verivication and draw the coclussion. The result of analisis showed that the society in development plan meeting in kelurahan setokok ran as societys expection. How ever, there were some inhibiting factors founds such as the societyss distrust on stakeholder its caused by the socio economic gap in each area. The important of development planing meeting (musrenbang) is to give the chance to society to partipate in democratic way. Therefore the the society aspiration can be sent to disstrict of batam government